Analysis of Knee-braced Portal Frames for Vertical Loading: Part 2-Columns of Unequal Stiffness - Vilas, Howard K.; Surtees, John O. (Engineering Journal, 1984)
In our previous paper, "The Analysis of Knee-Braced Portal Frames for Vertical Loading," the example presented had columns of equal stiffness, resulting in a simple computation for sway shear force. The sway shear force was equally divided between the two columns to find the knee-brace loads. This paper investigates the sway analysis of frames of unequal column stiffness. For continuity, the equation and figure numbers are continuous from Part 1. The first step in determining sway shear for the frame is described in the previous paper. Frame sway is first prevented by introducing a temporary horizontal restraint at the beam level. For a one bay portal frame, the initial kneebrace loads due to vertical loading are calculated using Eq. 7 of Ref. 1, and the restraint reactions determined. In the second step, the temporary restraint is removed and the frame allowed to sway due to the sway load, giving the sway correction. The sum of the two steps gives the required result.